Escola Família Agrícola e reprodução social construindo caminhos de resistência: construindo caminhos de resistência - Souza, Erika Fernanda Pereira de (2019)
The present work "School Family Agricultural and peasant social reproduction: constructing ways of resistance", built through the qualitative research, focuses on the conditions of insertion and professional, productive and social performance of the young graduates of the School Family Agricultural Nova Esperança , inserted in the Alto Rio Pardo Territory, a micro-region of the North of Minas Gerais, in its contradictions and the increase in the material conditions of life resulting from the process of insertion of agrarian capitalism in the state. These transformations culminated in the political and social organization in the region and in the consequent elaboration of the project of a school of the field that could be seen as one of the strategies of resistance and coexistence with the semiarid. The Agricultural Family School Nova Esperança in its 5 years of acting offering the high school integrated to the professional course of Agricultural Technician has already formed 132 young people, and now it is pertinent to question how the educational training developed at EFA Nova Esperança has contributed to the professional insertion, productive and social development of young graduates. In order to verify how the formation has collaborated in this sense, the work presented here presents a reflection on the "Movement for an Education of the Field" and the conditions of peasant social reproduction through a bibliographical review. The paths for consolidation of the Alternation Training Centers and the history of achievements and challenges of Field Education in MG were also explored. The analysis of the pedagogical political practice of the school was done through direct observation and bibliographical research, as well as semi-structured interviews, also directed to the graduates of the institution. It was possible to verify good indexes of professional and productive performance of young people, as well as positive results of access to higher education, work in social movements and permanence in the field, considering the intense structural challenges for social reproduction in the territory and the need for strengthening and articulation among social movements in the search for better living conditions in the countryside.